The Socio-Economic Value of Natural Riverbanks in the Netherlands - E.C.M. Ruijgrok; E.E.M. Nillesen (Fondazione Eni Enrico Mattei (FEEM), 2004)
Ecologists and economists both use a different approach to determine the value of nature. Its ecological value can be measured using criteria like rarity and diversity of species in an ecosystem. The economic value can be determined using non-market valuation techniques. This paper focuses on an empirical application of the Contingent Valuation Method (CVM) to find out whether this valuation method is a suitable method to estimate the economic value of natural riverbanks in the Netherlands. Natural riverbanks will provide habitat for species that particularly depend on the land water transit area. Since common riverbanks do not provide this habitat, natural river banks increase biodiversity in the Netherlands. On the basis of technical and ecological characteristics nine different types of natural riverbanks were distinguished. For each type a laymen description was made. This description served as a basis for economic valuation by means of CVM. The results of the CVM study shows that the average willingness to pay for non-use of a natural riverbank varied between 16 and 25 Dutch guilders per household year. The willingness to pay for recreational use ranged from 1,07 to 2,50 guilders per visit. The generated outcomes proved to be consistent with results from other studies. At first sight, the economic value of natural riverbanks seemed to be higher than their construction and maintenance cost.
Keywords: R14; Q25; 330; Nature friendly river banks; Land water interactions; Economic value; Nature; CVM; Non-use value; Fluss; Feuchtgebiet; Zahlungsbereitschaftsanalyse; Bewertung; Niederlande